Alignment of business and IT strategy in the travel industry in South Africa - Cronje, Willem (My University, 2014)
ABSTRACT Information technology has transformed business processes during the last several decades. It has changed its orientation from a pure operational utility to that of a competitive advantage. Aligning a firms business and IT strategy provides unique strategic business opportunity. Many companies still fail to properly align business and IT strategy and many IT and Business executives see it as an impossible goal to achieve. The purpose of this research is to identify factors that that influence alignment of business and IT strategy in the IT industry in South Africa. Data was collected using discussions in semi-structured interviews that were administered personally by the researcher. The 16 interviewees were from representatives from varied organisations across the travel industry who were actively and directly involved in IT of business strategy development. From the literature 5 factors that influence alignment was identified. It was found that 3 of the five factors that influence alignment were relevant to achieving alignment, 1 factor was seen as being less relevant and one factor as almost irrelevant.
MBA Thesis 2013
Keywords: Information technology, Management, Strategic planning, Travel agents